Students’ Translating Humor of Mind Your Language British Comedy in The Indonesian Subtitle - Lilik Istiqomah (Pustabiblia: Journal of Library and Information Science, 2017)
Subtitling becomes the most prominent growth in translation studies with its many advantages. It is cheaper than dubbing, take a short time, has the original soundtrack, better for hard-of-hearing and has a role in language learning. Subtitling can not be separated from the text. This text will be influenced by the context of a situation and also a context of culture. Having Cross Cultural Understanding better will show the ideology of the text. This study observes the translation technique of translating humor in Indonesian subtitle in the first episode of Mind Your Language British comedy series. This subtitle is done by the sixth-semester Indonesian students of English Education Program of Diamond Institute. This is a qualitative descriptive research presenting a translation unit tangible form in lingual (word, phrase, clause, and sentence) as the data. The object of the research is film dialogue in English and Indonesian subtitles also. The analysis of this study represents that there are 5 techniques in translating humor, namely Translating humor in wordplay with a literal translation, Translating humor in Source Text Pun with Target Text Pun, Translating humor in wordplay with wordplay, Translating humor in wordplay with zero wordplays (non-wordplay) and Translating humor with allusion. The use of literal translation technique is dominant while the ideal translation technique in translating humor is wordplay with wordplay.Subtitling mengalami pertumbuhan yang sangat pesat dalam studi penerjemahan dengan banyak kelebihannya. Subtitling lebih murah dari dubbing ditinjau dari segi biaya, proses pembuatannya tidak memerlukan waktu lama, mempunyai soundtract asli, dan lebih baik bagi para penderita tuna rungu dan sulit mendengar. Subtitling tidak bisa dipisahkan dari teks. Teks ini yang akan diperngaruhi oleh konteks situasi dan juga konteks budaya. Memiliki pandangan yang baik tentang Cross Cultural Understanding / perbedaan budaya akan bisa memahami ideologi teks tersebut. Penelitian ini mengkaji teknik penerjemahan humor dalam bahasa Indonesia dalam serial komedi Inggris yang berjudul “ Mind Your Language” episode pertama. Subtitle film komedi ini dikerjakan oleh mahasiswa semester enam jurusan Pendidikan Bahasa Inggris. Penelitian ini adalah penelitian deskriptif kualitatif yang mengetengahkan unit penerjemahan bentuk lingual (kata, frasa, klausa, dan kalimat). Objek penelitian ini adalah dialog film dalam bahasa Inggris dan bahasa Indonesi. Analisis dalam pene- litian ini menunjukkan bahawa ada 5 teknik dalam menerjemahkan humor, yaitu merjemahkan humor dalam wordplay dengan perjemahan literal, menerjemahkan humor dalam permainan kata kata (pun) bahasa sumber ke dalam pun bahasa sasa- ran, menerjemahkan wordplay dengan wordplay, menerjemahkan wordplay dengan cara tanpa menerjemahkannya (dibiarkan apa adanya) dan menerjemahkan humor dengan allusion (kiasan). Penggunaan teknik penerjemahan literal sangat dominan sedangkan teknik terjemahan yang ideal dalam menerjemahkan humor adalah wordplay dengan wordplay.